Activation of cGAS‐STING by Lethal Malaria N67C Dictates Immunity and Mortality through Induction of CD11b+Ly6Chi Proinflammatory Monocytes. Issue 22 (29th May 2022) - Du, Yang; Luo, Yien; Hu, Zhiqiang; Lu, Jiansen; Liu, Xin; Xing, Changsheng; Wu, Jian; Duan, Tianhao; Chu, Junjun; Wang, Helen Y.; Su, Xin‐zhuan; Yu, Xiao; et al.
Abstract: Cyclic GMP‐AMP synthase (cGAS) and stimulator of interferon genes (STING) play critical roles in the innate immunity against infectious diseases and are required to link pathogen DNA sensing to immune responses. However, the mechanisms by which cGAS‐STING‐induced cytokines suppress the adaptive immune response against malaria infections remain poorly understood. Here, cGAS‐STING signaling is identified to play a detrimental role in regulating anti‐malaria immunity. cGAS or STING deficiency in mice markedly prolongs mouse survival during lethal malaria Plasmodium yoelii nigeriensis N67C infections by reducing late interleukin (IL)‐6 production. Mechanistically, cGAS/STING recruits myeloid differentiation factor 88 (MyD88) and specifically induces the p38‐dependent signaling pathway for late IL‐6 production, which, in turn, expands CD11b + Ly6C hi proinflammatory monocytes to inhibit immunity. Moreover, the blockage or ablation of the cGAS‐STING‐MyD88‐p38‐IL‐6 signaling axis or the depletion of CD11b + Ly6C hi proinflammatory monocytes provides mice a significant survival benefit during N67C and other lethal malaria‐strain infections. Taken together, these findings identify a previously unrecognized detrimental role of cGAS‐STING‐MyD88‐p38 axis in infectious diseases through triggering the late IL‐6 production and proinflammatory monocyte expansion and provide insight into how targeting the DNA sensing pathway, dysregulated cytokines, and proinflammatory monocytes enhances immunity against infection. Abstract : Cyclic GMP‐AMP synthase (cGAS) and stimulator of interferon genes (STING) play critical roles in innate immunity against infectious diseases, while the mechanisms that cGAS‐STING‐induced cytokines suppress immune response against malaria infection remain poorly understood. Here, this study reveals that cGAS‐STING signaling plays a detrimental role in regulating anti‐malaria immunity by cooperating with MyD88 to induce p38‐dependent late IL‐6 production and expanding CD11b + Ly6C hi proinflammatory monocytes.